2017
DOI: 10.21276/ijircst.2017.5.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Global Exponential Stability and Stabilization of Fractional-Order Positive Switched Systems

Abstract: Abstract-This paper is concerned with the global exponential stability(GES) and stabilization of fractional-order positive switched systems(FOPSS) with average dwell time(ADT). Firstly, the the concept of GES is extended to FOPSS. Then, by constructing copositive Lyapunov functions and using ADT approach, a state feedback controller is constructed, and sufficient conditions are derived to guarantee that the corresponding closed-loop system is globally exponentially stable. Such conditions can be easily solved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, there are many differences between integer order systems and fractional order systems, which lead to different proof processes. We also know that FOSS are more complex and challenging (Cao et al, 2016; Liu et al, 2017a; Zhang et al, 2017), as also shown by the proof of Theorem 11.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, there are many differences between integer order systems and fractional order systems, which lead to different proof processes. We also know that FOSS are more complex and challenging (Cao et al, 2016; Liu et al, 2017a; Zhang et al, 2017), as also shown by the proof of Theorem 11.…”
Section: Resultsmentioning
confidence: 80%
“…FTS and stabilization of fractional order positive switched system are reported by Zhang et al (2017). Global exponential stability and stabilization of fractional order positive switched system are given by Cao et al (2016). These three papers are about positive switched systems.…”
Section: Introductionmentioning
confidence: 99%